Urgency Of Village Owned Enterprises (Bumdes) In Village Economic Development - Siti Zulaikah (Tamilis Synex: Multidimensional Collaboration, 2023)
The purpose of this paper is to describe the importance of village-owned enterprises and their management for the benefit of rural communities. By referring to the legislation regulating rural areas, especially Law No. According to Law No. 6 of 2014, it can be concluded that a village-owned enterprise is a village economic institution that has an important role in the well-being of the community, the village, and the village government. Professional governance referring to the guidelines for the formation of village-owned enterprises on the basis of legislation is a prerequisite for the proper functioning of village-owned enterprises. Hence, the economic activities of village-owned enterprises should be part of efforts to increase local and regional economies within the scope of the national economy.